Morphology of Mandibular First Molars Analyzed by Cone-beam Computed Tomography in a Korean Population: Variations in the Number of Roots and Canals - Kim, Sin-Young; Kim, Bom Sahn; Woo, Jein; Kim, Yemi (Journal of endodontics, 2013)
The aim of this study was to determine the root and canal morphology of the mandibular first molars in a Korean population of Mongolian origin by retrospective analysis of a large number of cone-beam computed tomography (CBCT) images. A total of 976 subjects with bilateral mandibular first molars were examined by using in vivo CBCT methods. The number and configuration of roots, the number of root canals, and the canal configuration based on Vertucci's classification were determined. Overall, 25.82% of examined molars had 3 roots, 73.51% had 2 roots, and 0.67% had 1 root. The incidence of fourth canal was 50.36%. A right-sided predominance was noted for extra distal roots (P < .001), whereas a left-sided predominance was observed for extra distal canals (P < .001). No significant sex-related differences were shown for their prevalence. The bilateral prevalence rate was 69.13% for extra distal roots and 78.08% for extra distolingual (DL) canals. In the mesial roots, type IV canal was the most frequent (76.86% for 2-rooted molars and 72.96% for 3-rooted molars). In the distal roots, type l was the most common (66.62% for 2-rooted molars and 99.40%–100% for 3-rooted molars). The incidence of 2 canals in distobuccal roots, first reported in this study, was 0.15%. Among mandibular first molars, there is a high prevalence of a separate DL root and/or a separate DL canal, and such molars commonly have 4 canals in the Korean population. CBCT is a useful tool for determining root and canal morphology.